Exercise induced changes in autonomic nerve function in patients with irritable bowel syndrome by power spectral analysis - Tenzin, Karma; Begum, Noorzahan; Ferdousi, Sultana (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Altered autonomic nerve function has been reported by various investigators in IBS and moderate to vigorous physical exercise causes autonomic nerve function improvement both in healthy and various clinical conditions. Objective: To observe the effect of brisk walking on the autonomic nerve function by analysis of heart rate in patients with Irritable bowel syndrome. Methods: This prospective interventional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU) between January to December 2013. For this purpose 77 male patients aged 20-50 years with IBS were included in this study, they were enrolled from OPD, Gastroenterology, BSMMU, Dhaka. For comparison, 28 apparently healthy male were also included as control. HRV measures were recorded once before exercise and also after 3 months of brisk walking. For assessing HRV, frequency domain measures such as total power, LF power, HF power, LF norm and HF norm were recorded by Polyrite D machine. ANOVA, Independent sample t-test and paired t-tests were performed for statistical analysis. Results: The pre-exercise values of HF power, HF norm and total power were significantly lower (p<0.05) whereas values of LF power and LF norm were higher (p<0.05) in all IBS patient compared to those of control. The post exercise data demonstrated significantly higher (p<0.05) HF power, HF nu and total power in all IBS patients compared to their pre-exercise values. Conclusion: This study concluded that the frequency domain measures of HRV were decreased in IBS patients but all these parameters can be improved by regular moderate physical exercise.